Optimization of in vitro fertilization technique for oocytes of indigenous zebu cows - Mohammad Moshiur Rahman; Md. Masudur Rahman; Nasrin Sultana Juyena; Mohammad Musharraf Uddin Bhuiyan (Journal of Animal Reproduction and Biotechnology, 2020)
The research work was undertaken to determine an effective fertilization medium, sperm separation method and sperm capacitating agent for optimum in vitro fertilization (IVF) rates of indigenous zebu cow oocytes. In experiment 1, tissue culture medium (TCM 199), Tyrode’s albumin lactate pyruvate (TALP) and Brackett and Oliphant (BO) medium were used as basic medium for IVF of oocytes of indigenous zebu cows. In experiment 2, three sperm separation methods namely centrifugation, swim up and percoll gradient methods were used for separation of motile and viable spermatozoa for IVF. In experiment 3, for capacitation of spermatozoa, IVF medium supplemented with the heparin, mixture of penicillamine, hypotaurine and epinephrine (PHE) or the combination of heparin with PHE were used for fertilization. In vitro culture (IVC) of presumptive zygotes was done in modified synthetic oviduct fluid (mSOF) medium using standard procedure 24 h after sperm-oocytes co-culture. The cleavage rate was determined to evaluate the efficacy of fertilization medium, sperm separation method and sperm capacitating agent 24 h after IVC. The cleavage rate was higher in oocytes fertilized in TALP (63.3%) than in TCM 199 (47.5%) (p < 0.05). The cleavage rate was higher in oocytes fertilized by spermatozoa separated by percoll gradient method (62.3%) than by centrifugation (51.6%) (p < 0.05). The cleavage rate of oocytes was higher when insemination was done with spermatozoa capacitated in TALP supplemented with heparin and PHE (61.3%) compared to control (40.9%) (p < 0.05). In conclusions, TALP based medium and percoll gradient sperm separation followed by capacitation with combination of heparin and PHE are suitable for IVF of indigenous zebu cow oocytes in Bangladesh.